Auxetic metamaterial optimisation for head impact mitigation in American football. (November 2021) - Hanna, Benjamin; Adams, Rhosslyn; Townsend, Scott; Robinson, Michael; Soe, Shwe; Stewart, Matthew; Burek, R.; Theobald, Peter
Highlights: Miura Ori cellular structure investigated as a potential protective material. Taguchi methodology enabled efficient investigation of mulitple parameters. Linear impacts at 3 velocities performed to simulate American football collisions. Novel approach to defining performance via single outcome measure. Final structure more efficient than helmet-derived foam across 3 impact velocities. Abstract: American football has a comparatively high rate of sports-related concussions, despite mitigating strategies including the use of protective helmets. The traditional energy absorbing component, elastomeric foam pads, have limited scope for leveraging any further protection. Alternative structures and materials that exhibit novel deformation mechanics have been proposed as a route to increased energy absorption capacity. This study investigated a metamaterial based on the Miura Ori folding pattern. Eighty-one potential structural variations were conceptualised and evaluated via the Taguchi method. Twenty-seven geometries were then additively manufactured using commercially available thermoplastic polyurethane, before being impacted at multiple velocities. Experimental data were then extrapolated to predict the impact behaviour across all 81 variants. An optimised geometry was then proposed, which reduced linear accelerations across the test conditions and performed favourably when compared to current, elastomeric foam solutions. This work provides a promising foundation for future investigation.